The Legionella pneumophila effector PieF modulates mRNA stability through association with eukaryotic CCR4−NOT - Harley O'Connor Mount; Malene L. Urbanus; Francesco Zangari; Anne-Claude Gingras; Alexander W. Ensminger (mSphere)
ABSTRACT The eukaryotic CCR4−NOT deadenylase complex is a highly conserved regulator of mRNA metabolism that influences the expression of the complete transcriptome, representing a prime target for a generalist bacterial pathogen. We show that a translocated bacterial effector protein, PieF (Lpg1972) of Legionella pneumophila, directly interacts with the CNOT7/8 nuclease module of CCR4−NOT, with a dissociation constant in the low nanomolar range. PieF is a robust in vitro inhibitor of the DEDD-type nuclease, CNOT7, acting in a stoichiometric, dose-dependent manner. Heterologous expression of PieF phenocopies knockout of the CNOT7 ortholog (POP2) in Saccharomyces cerevisiae, resulting in 6-azauracil sensitivity. In mammalian cells, expression of PieF leads to a variety of quantifiable phenotypes: PieF silences gene expression and reduces mRNA steady-state levels when artificially tethered to a reporter transcript, and its overexpression results in the nuclear exclusion of CNOT7. PieF expression also disrupts the association between CNOT6/6L EEP-type nucleases and CNOT7. Adding to the complexities of PieF activity in vivo, we identified a separate domain of PieF responsible for binding to eukaryotic kinases. Unlike what we observe for CNOT6/6L, we show that these interactions can occur concomitantly with PieF’s binding to CNOT7. Collectively, this work reveals a new, highly conserved target of L. pneumophila effectors and suggests a mechanism by which the pathogen may be modulating host mRNA stability and expression during infection.IMPORTANCEThe intracellular bacterial pathogen Legionella pneumophila targets conserved eukaryotic pathways to establish a replicative niche inside host cells. With a host range that spans billions of years of evolution (from protists to humans), the interaction between L. pneumophila and its hosts frequently involves conserved eukaryotic pathways (protein translation, ubiquitination, membrane trafficking, autophagy, and the cytoskeleton). Here, we present the identification of a new, highly conserved host target of L. pneumophila effectors: the CCR4−NOT complex. CCR4−NOT modulates mRNA stability in eukaryotes from yeast to humans, making it an attractive target for a generalist pathogen, such as L. pneumophila. We show that the uncharacterized L. pneumophila effector PieF specifically targets one component of this complex, the deadenylase subunit CNOT7/8. We show that the interaction between PieF and CNOT7 is direct, occurs with high affinity, and reshapes the catalytic activity, localization, and composition of the complex across evolutionarily diverse eukaryotic cells.